The relationship between personality traits, positive affect and work engagement among Malaysian white-collar employees - Abu Saiid, Dania (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The purpose of the present study is to determine the influence of the Big Five personality traits and positive affect on work engagement. Positive affect here refers to the extent of positive emotions or positive moods felt by a person. A total of 103 white-collar Malaysian employees were surveyed. Hierarchical multiple regression indicates that the best fitting model is a linear combination of extraversion, agreeableness and positive affect which together explains 36% of the variance in work engagement. Positive affect predicts work engagement over and above extraversion and agreeableness. Mediation analysis using Baron and Kenny's (1989) and Kenny's (2016) causal steps and Preacher and Hayes's (2004) bootstrapping approach further suggest that positive affect also partially mediates the relationship between each of the Big Five personality traits and work engagement. The results highlight the significant role positive affect plays in the work engagement of white-collar Malaysians. Extraversion and agreeableness are likely to increase their work engagement. However, having positive affect due to these traits is likely to further enhance their work engagement. Conscientiousness and openness are not likely to make much significant difference in their work engagement. However, any positive affect produced from these traits is likely to improve their work engagement. Meanwhile, neuroticism is not likely to have any significant influence on their work engagement. However, if it decreases their level of positive affect, this is likely to decrease their work engagement. The distinct results in this study, (when comparing with literature), point to the possibility of cultural influence on the relationship between personality traits and work engagement of an employee. The results may be used by both the employer and employee by taking personality traits and positive affect into consideration during selection, delegation of tasks, activities, training and interventions.